Influenza A surface glycosylation and vaccine design - Chung‐Yi Wu; Chih-Wei Lin; Tsung-I Tsai; Chang‐Chun D. Lee; Hong-Yang Chuang; Jhih-Bin Chen; Ming‐Hung Tsai; Bo-Rui Chen; Pei-Wen Lo; Chiu-Ping Liu; Vidya S. Shivatare; Chi‐Huey Wong (2016)
Significance Influenza A virus (IAV) is a major threat to global public health, and so understanding the biology of IAV is essential to develop antiflu vaccines and therapeutics. Here, we show the links between viral surface glycosylation and IAV function. The glycosylation of HA modulates virus infectivity, and host immune response; the glycosylation of NA affects its structure, activity, specificity, and thermostability to regulate virus release and virulence. In addition, using live attenuated IAV without the stalk and catalytic domains of NA as vaccine can strongly induce IAV-specific CD8 + T-cell responses to various virus strains. Therefore, our findings have clarified the role of glycosylation in IAV and provided a new direction for the development of universal flu vaccines.